Assessment of nutritional knowledge of patients with pancreatitis - Włochal, Małgorzata; Swora-Cwynar, Ewelina; Karczewski, Jacek; Grzymisławski, Marian (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Proper nourishment is one of the basic elements in the treatment of patients with both acute and chronic pancreatitis. Following acute pancreatitis, the essential element of nutritional treatment is dietary education. The dietary approach is used not only for treatment, but also for prevention of reoccurrence of the condition. Aim: To evaluate nutritional knowledge of patients with acute and chronic pancreatitis. Material and methods : The selected group consisted of 36 patients, 19 females and 17 males, suffering from acute or chronic pancreatitis. Participation in our survey was anonymous and voluntary. The study population was divided into two groups: 12 patients with acute pancreatitis (5 males and 7 females) and 24 patients with chronic pancreatitis (12 males and 12 females). The median age of patients was 42.4 ±14 years (range: 20–76 years). The duration of illness among the study population was varied. The biggest group of 16 (44.4%) patients suffered from pancreatitis for more than 5 years, 8 (22.2%) patients had pancreatitis diagnosed 1–2 years previously, only 3 (8.3%) subjects suffered from pancreatitis for shorter than half a year. To analyse patients’ nutritional knowledge an authorial questionnaire was used that contained 17 closed questions and open-type questions were used three times. Results : Most (97%) subjects with acute and chronic pancreatitis adhered to the diet to various degrees, but almost 50% of people up to 35 years of age declared that they didn’t respect the diet, or that they followed only a few recommendations. Despite each interviewer admitted to follow dietary recommendations for pancreatitis, 11.1% of patients could not indicate any of them. Most patients knew that their diet should contain a low amount of fat (61% of patients). Awareness of alcohol abstinence was confirmed in 44.4% of subjects. One third (33.3%) of patients knew that fried food should be avoided. Only a few patients were aware that smoking, spicy food, and strong coffee should be excluded from their diet. About 80% of the surveyed patients evaluated their level of nutritional knowledge as good or very good. Only 20% of the study population admitted their dietary knowledge was unsatisfactory, and most of these were woman (86%). Conclusions : The results of the present study demonstrate that dietary knowledge among patients suffering from acute and chronic pancreatitis is insufficient. Although patients have theoretical knowledge about nutritional management, they have problems implementing the diet on a daily basis. It is necessary to pay more attention to nutritional education for patients suffering from pancreatitis.